In Situ Sprayed Starvation/Chemodynamic Therapeutic Gel for Post‐Surgical Treatment of IDH1 (R132H) Glioma. Issue 5 (12th December 2021) - Li, Chunying; Wan, Yilin; Zhang, Yifan; Fu, Lian‐Hua; Blum, Nicholas Thomas; Cui, Run; Wu, Boda; Zheng, Rui; Lin, Jing; Li, Zhiming; Huang, Peng
Abstract: Complete resection of isocitrate dehydrogenase 1 (IDH1) (R132H) glioma is unfeasible and the classic post‐surgical chemo/radiotherapy suffers from high recurrence and low survival rate. IDH1 (R132H) cells are sensitive to low concentrations of glucose and high concentrations of reactive oxygen species (ROS) due to inherent metabolism reprograming. Hence, a starvation/chemodynamic therapeutic gel is developed to combat residual IDH1 (R132H) tumor cells after surgery. Briefly, glucose oxidase (GOx) is mineralized with manganese‐doped calcium phosphate to form GOx@MnCaP nanoparticles, which are encapsulated into the fibrin gel (GOx@MnCaP@fibrin). After spraying gel in the surgical cavity, GOx catalyzes the oxidation of glucose in residual IDH1 (R132H) cells and produces H2 O2 . The generated H2 O2 is further converted into highly lethal hydroxyl radicals (OH) by a Mn 2+ ‐mediated Fenton‐like reaction to further kill the residual IDH1 (R132H) cells. The as‐prepared starvation/chemodynamic therapeutic gel shows much higher therapeutic efficacy toward IDH1 (R132H) cells than IDH1 (WT) cells, and achieves long‐term survival. Abstract : A starvation/chemodynamic therapeutic gel of GOx@MnCaP@fibrin is developed for post‐surgical treatment of isocitrate dehydrogenase 1 (IDH1) (R132H) glioma, through depleting intratumoral glucose and generating high levels of reactive oxygen species.